Lipid Nanocapsules for brain targeting of Nimodipine - Mohsen, Karim (AUC Knowledge Fountain, 2018)
Subarachnoid hemorrhage (SAH) is the leading cause of death in stroke patients who suffer from vasospasms with incidence of 70%. SAH prevents sufficient oxygen supply to the brain causing ischemia and death. FDA approved only nimodipine (NM) for treatment of vasospasm associated with SAH. Nevertheless, NM has poor pharmacokinetic properties, which limit its clinical efficacy. NM is susceptible to first-pass metabolism and has low solubility and thereby poor bioavailability. The objective of this study is to assess the nose-brain pathway in brain targeting of NM-loaded lipid nanocapsules (LNCs) after intranasal administration. Solvent-free phase inversion temperature technique was used to prepare NM-loaded LNCs. Design Expert 7 was used to establish D-optimal mixture design. The model evaluates the impact of individual and combined effects of three independent variables, X1 (Labrafac), X2 (Solutol HS 15), and X3 (water), on responses Y1 (particle size), Y2 (Zeta potential), Y3 (polydispersity index; PDI), Y4 (drug payload), Y5 (entrapment efficiency), Y6, Y7, and Y8 (in vitro drug release after 6, 24, and 48 h, resp.), and Y9 (solubilization capacity). NM-loaded LNC was optimized to increase the NM payload, decrease particle size, and fulfil suitable zeta potential, PDI, and in vitro drug release. The optimized NM-loaded LNC revealed narrow size distribution of PDI of 0.146 Â± 0.045, small particle size of 35.94 Â± 0.14 nm, 5 mg/mL drug payload, spherical morphology, and appropriate drug release profile initially and over a 3-month period. The in vivo pharmacokinetic assessment of optimized NM-loaded LNC revealed absolute bioavailability of NM in brain (99.5%) and plasma (102.6%) in Wistar rats after intranasal administration of NM-loaded LNCs with reference to the IV administered NM solution. Finally, intranasal administration of NM-loaded LNCs supported safe and effective practice to deliver NM via intranasal route to the brain via systemic pathway attributed with NM BBB enhancement.